2015
DOI: 10.1787/5jrxhgjw54r8-en
|View full text |Cite
|
Sign up to set email alerts
|

Economic resilience: A new set of vulnerability indicators for OECD countries

Abstract: Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. ECO/WKP(2015)67 Unclassified English-Or. English ECO/WKP(2015)67 2 OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…To help governments to detect vulnerabilities early, Röhn, O. et al (2015) proposed a set of vulnerability indicators grouped into six areas: financial sector, non-financial sector, asset market, public sector, external sector, and international spillovers, contagion and global risks.…”
Section: Introductionmentioning
confidence: 99%
“…To help governments to detect vulnerabilities early, Röhn, O. et al (2015) proposed a set of vulnerability indicators grouped into six areas: financial sector, non-financial sector, asset market, public sector, external sector, and international spillovers, contagion and global risks.…”
Section: Introductionmentioning
confidence: 99%
“…Other international organisations, such as the IMF, have gone further in publishing forecast ranges, fan charts and assessments of the likelihood of the occurrence of particular events, such as recession or deflation. The OECD has also recently been carrying out work to evaluate the usefulness of early warning indicators which can signal the probability of an imminent severe recession or crisis [Hermansen and Röhn (2015); Röhn et al (2015)], although this has not yet been incorporated as part of the regular commentary around the central forecast. Such developments, which explicitly recognise the inevitable uncertainty around global macroeconomic forecasts, appear particularly appropriate given the paucity of the forecast track-record beyond the current year, especially in predicting downturns.…”
mentioning
confidence: 99%
“…In order to do so, the paper draws heavily on recent OECD work of the Resilience workstream of the Economics Department. Röhn et al (2015) establish a database of more than 70 vulnerability indicators that are identified as particularly relevant for OECD countries based on a thorough review of the most recent evidence from the early warning literature and lessons learned from the global financial crisis. The indicators are grouped into five areas of domestic vulnerabilities: i) financial sector imbalances, ii) non-financial sector imbalances, iii) asset market imbalances, iv) public sector imbalances, v) external sector imbalances.…”
mentioning
confidence: 99%
“…Hermansen and Röhn (2015) provide empirical evidence on the usefulness of these vulnerability indicators in predicting severe GDP per capita recessions and crises in OECD countries. In this paper we draw on the new database of Röhn et al (2015) and apply the same methodology as in Hermansen and Röhn (2015). In particular, we employ the signalling approach, a commonly used methodology, to detect vulnerability indicators that could perform particularly well in the Turkish context.…”
mentioning
confidence: 99%
See 1 more Smart Citation